Partial denture swallowed by patient with dementia. (17th June 2015) - Saunders, Ralph
ABSTRACT Purpose To present a rare case of a male dementia patient in a nursing home who swallowed a partial denture which lodged in the airway. Methods During breakfast, a patient with moderate dementia experienced a sore throat, labored breathing, and difficulty swallowing. Uncertainty about the cause of these problems was exacerbated by the patient's cognitive losses, his reduced oro‐motor function, and awareness of caregivers that the possible involvement of a denture of this size was unlikely. At the beginning of the third day, he developed a low‐grade fever and was placed on antibiotics. A chest x‐ray was negative. Results On the fourth day, a flexible endoscopic evaluation of swallowing was performed, which revealed the partial denture resting in the hypopharynx on the patient's vocal cords. Discussion Along with pneumonia and viral bronchitis, a swallowed denture needs to be in the differential diagnosis of a dementia patient experiencing difficulty swallowing. Conclusions Nursing home caregivers be aware that even a sizable partial denture can be swallowed and extra vigilance is essential in caring for dementia patients.